ЗОЛЬ-ГЕЛЬ СИНТЕЗ И ИЗУЧЕНИЕ СВОЙСТВ НАНОЧАСТИЦ ОКСИДА ТАНТАЛА (V) ДЛЯ ПРИМЕНЕНИЯ В ОНКОТЕРАНОСТИКЕ - Назаровская, Дарья Андреевна; Кошевая, Екатерина Дмитриевна; Фахардо, Анна Фабиовна; Кривошапкина, Елена Фёдоровна; Кривошапкин, Павел Васильевич (Медицина: теория и практика, 2020)